Long-term survival in primary glioblastoma with versus without isocitrate dehydrogenase mutations - Hartmann, Christian; Deimling, Andreas von (Clinical cancer research, 2013)
Purpose: The determinants of long-term survival in glioblastoma have remained largely obscure. Isocitrate dehydrogenase (IDH) 1 or 2 mutations are common in World Health Organization (WHO) grades II and III gliomas, but rare in primary glioblastomas, and associated with longer survival. - Experimental Design: We compared clinical and molecular characteristics of 69 patients with centrally confirmed glioblastoma and survival >36 months (LTS-36), including 33 patients surviving >60 months (LTS-60), with 257 patients surviving <36 months. MGMT promoter methylation, 1p/19q codeletions, EGFR amplification, TP53 mutations, and IDH1/2 mutations were determined by standard techniques. - Results: The rate of IDH1/2 mutations in LTS-36 patients was 34% (23 of 67 patients) as opposed to 4.3% in controls (11 of 257 patients). Long-term survivors with IDH1/2-mutant glioblastomas were younger, had almost no EGFR amplifications, but exhibited more often 1p/19q codeletions and TP53 mutations than LTS patients with IDH1/2 wild-type glioblastomas. Long-term survivors with IDH1/2 wild-type showed no distinguishing features from other patients with IDH1/2 wild-type glioblastomas except for a higher rate of MGMT promoter methylation. Similarly, among 11 patients with IDH1/2-mutant glioblastomas without long-term survival, the only difference to IDH1/2-mutant long-term survivors was less-frequent MGMT promoter methylation. Compared with LTS-36 patients, LTS-60 patients had less frequently TP53 mutations and radiotherapy alone as initial treatment. - Conclusions: IDH1/2 mutations define a subgroup of tumors of LTS patients that exhibit molecular characteristics of WHO grade II/III gliomas and secondary glioblastomas. Determinants of LTS with IDH1/2 wild-type glioblastomas, which exhibit typical molecular features of primary glioblastomas, beyond MGMT promoter methylation, remain to be identified. Clin Cancer Res; 19(18); 5146-57. ©2013 AACR.
Gesehen am 08.10.2021